Honor killings in the twenty-first century - Pope, Nicole (Palgrave Macmillan, 2011)
Thousands of women are murdered every year by close relatives for allegedly violating an unwritten social code or rebelling against the patriarchal order. Other harmful practices such as forced marriage, child marriage, or bride exchange have been recorded for centuries and adapted to modern times. The book examines honor-based violence, its roots and its evolution, as well as the ongoing struggle to eradicate it in Turkey, Pakistan and other countries, including Western European nations.